FRIEND, PARTNER, AND WIFE (E.N. SAKHAROVA AND N.I. VAVILOV) - M. A. Vishnyakova (Вавиловский журнал генетики и селекции)
The paper is dedicated to Ekaterina Sakharova, N.I. Vavilov’s fellow student at the Moscow Agricultural Institute, who later became his wife. She was reputed to be «the star» of the Institute. Previously unknown information about her life and work is presented. Sakharova signified her professional career as «an agronomist-teacher-adviser». In addition, she was a translator, journalist, sociologist, and social worker. She also took part in political activities. She communicated with conspicuous people of the first half of the 20th century. Her role in Vavilov’s life is discussed. A list of her publications has been compiled for the first time.